2005
DOI: 10.1164/rccm.200412-1698oc
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione-S-Transferase M1, Obesity, Statins, and Autonomic Effects of Particles

Abstract: Rationale: Air pollution by particulate matter (PM) has been associated with cardiovascular deaths, although the mechanism of action is unclear. One proposed pathway is through disturbances of the autonomic control of the heart. Objectives: We tested the hypothesis that such disturbances are mediated by PM increasing oxidative stress by examining the association between PM and the high-frequency (HF) component of heart rate variability as modified by the presence or absence of the allele for glutathione-S-tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
178
3
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 188 publications
(193 citation statements)
references
References 59 publications
8
178
3
4
Order By: Relevance
“…As observed in the case of cigarette smoke, a significant source of oxidative stress, air pollutants would lower antioxidant defences, with deleterious health consequences [116,117]. Evidence of the potential beneficial effect of antioxidants can be found in studies of elderly subjects in which treatment with statins [108] and n-3 PUFA supplementation [106] had a beneficial effect on response to particulate exposure.…”
Section: Chronic Diseasesmentioning
confidence: 97%
See 4 more Smart Citations
“…As observed in the case of cigarette smoke, a significant source of oxidative stress, air pollutants would lower antioxidant defences, with deleterious health consequences [116,117]. Evidence of the potential beneficial effect of antioxidants can be found in studies of elderly subjects in which treatment with statins [108] and n-3 PUFA supplementation [106] had a beneficial effect on response to particulate exposure.…”
Section: Chronic Diseasesmentioning
confidence: 97%
“…In a randomised trial conducted in nursing home residents, supplementation with 2 g?day -1 of fish oil (each 1 g capsule contained 83.2 % of omega-3 fatty acids) significantly decreased the effect of PM2.5 on time and frequency domain parameters of HRV [106] This is one of two studies providing evidence that oxidant stress is one of the mechanisms explaining the effect of particle air pollution on the cardiovascular system [107]. The other study reported that statins had a mitigating effect on the HRV effects of particulate air pollution in subjects genetically susceptible to oxidative stress (lacking the GSTM1 allele) [108].…”
Section: Cardiovascular Effectmentioning
confidence: 98%
See 3 more Smart Citations